Influência da textura do endosperma nas características físicas, na composição nutricional e na concentração de micotoxinas em grãos de milho cultivados no Brasil - Simões, Cristina Tonial (2024)
This thesis aims to evaluate the influence of endosperm texture on the nutritional composition, physical characteristics, and mycotoxin concentration in different types of corn cultivated in Brazil. Corn with different endosperm textures were cultivated in the state of Paraná in 2020, 2021, and 2022. In 2020, 213 samples were separated into 4 groups according to the endosperm texture: dent, flint, semident, and semiflint. Crop yield and damaged grains were determined. Nutritional composition and energy values were predicted by near-infrared spectroscopy. Data were subjected to ANOVA, and means were separated by Tukey's test at 5% significance. Starch was higher (P < 0.01) in dent corn than in flint corn. Dent corn showed the highest percentage of damaged grains (P < 0.01). Flint corn had the lowest crop yield (P < 0.001); however, it had the highest levels of crude protein (CP) and total and digestible amino acids (AA) (P < 0.001). Energy values were not different among corn types (P > 0.05). In 2021, 216 corn samples were also separated into dent, flint, semident, and semiflint. Mycotoxin contamination of corn cultivated in 2020 and 2021 was evaluated. Mycotoxins were quantified by liquid chromatography coupled with mass spectrometry. Data were subjected to ANOVA, and means were separated by Tukey's test at 5% significance. In 2020, flint corn had the lowest concentration of fumonisins B1 (FB1), while dent corn had the highest concentration of FB1 and FB2 (P < 0.05). In 2021, dent corn showed the highest averages of FB1, FB2, and diacetoxyscirpenol (P < 0.05). Dent and semi-dent corns had the highest concentration of nivalenol (P < 0.05). In 2022, 80 corn samples were used to assess the relationship between grain hardness, nutritional composition, and mycotoxins concentration. Grain hardness was determined using a texture analyzer, where ten grains from each sample were individually placed on the platform and compressed until breakage. Then, corn grains were separated into three different groups according to their hardness: Group 1 (< 52 kgf), Group 2 (52 ≤ kgf < 54), and Group 3 (≥ 54 kgf). Hardness negatively correlated (P < 0.05) with fumonisins and starch, and positively correlated (P < 0.05) with CP and total AA. Group 3 had lower fumonisin concentration and higher CP and AA than Groups 1 and 2 (P < 0.05). Therefore, it is concluded that the endosperm texture influences field characteristics, nutritional composition, and mycotoxin contamination in grains of different corn types. Furthermore, results of this study suggest that the higher the grain hardness, the higher its CP and AA content, and the lower its fumonisins contamination levels.